Refractory material and preparation method thereof, and glass kiln

By using the synergistic action of multiple raw materials and reasonable particle size distribution, a high-performance refractory material was prepared, which solved the problem of poor thermal shock resistance of existing refractory materials and achieved excellent performance and long life in high temperature environments.

CN119751034APending Publication Date: 2025-04-04东旭药玻(北京)科技有限公司 +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411687041.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing refractory materials for glass kilns have poor thermal shock resistance, which leads to the rapid temperature change and the durability and reliability of the material.

Method used

A refractory material formula is adopted, including silicon sol, white corundum, aluminum nitride powder, silica powder, aluminum titanate, zirconium oxide, barium sulfate, borax, mica powder and magnesium oxide. The adhesion, density and thermal conductivity of the material are enhanced through reasonable particle size distribution and preparation methods.

Benefits of technology

The refractory material exhibits excellent compressive resistance, flexural strength and thermal shock stability under high temperature environments, has strong chemical stability and high adaptability, extends service life and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005150190350000161
    Figure BDA0005150190350000161
  • Figure BDA0005150190350000171
    Figure BDA0005150190350000171
  • Figure BDA0005150190350000181
    Figure BDA0005150190350000181
Patent Text Reader

Abstract

The present application relates to a refractory material and a preparation method thereof, and a glass kiln, and belongs to the technical field of refractory materials. A refractory material, in parts by weight, includes: 40-50 parts of silica sol, 15-20 parts of white corundum, 3-4 parts of aluminum nitride powder, 5-8 parts of silicon dioxide powder, 3-5 parts of aluminum titanate, 5-8 parts of zirconium oxide, 5-8 parts of barium sulfate, 3-5 parts of borax, 1-2 parts of muscovite powder, 1-2 parts of magnesium oxide, and 1-3 parts of butanediol; wherein the mass concentration of silicon dioxide in each part of silica sol is 40-45%. The present application, through the synergistic effect between the above raw materials, makes the refractory material have the advantages of high refractoriness, excellent compressive and flexural strength, good thermal shock stability, strong chemical stability, and strong adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of refractory materials, and in particular to a refractory material and a preparation method thereof, and a glass kiln. Background Art

[0002] The main raw materials of glass are quartz sand and soda ash, which are melted at high temperatures to form glass. Glass kilns are key equipment for melting glass. Currently, there are many types of glass kilns on the market, such as tank kilns, crucible kilns, etc. However, these kilns face significant challenges during use. The lining of the kiln is usually subject to severe physical wear and chemical erosion, especially in a high-temperature melting environment, where molten glass and its raw materials are highly corrosive.

[0003] During the continuous melting of glass production, the refractory lining is constantly subjected to thermal stress, which often causes scratches and cracks. These cracks will expand over time and eventually lead to the outflow of molten glass, which seriously affects the service life of the refractory. The temperature of the furnace, the degree of chemical attack, the operating speed and the type of molten glass used are closely related to the refractory performance of the lining.

[0004] Although existing glass furnace refractories have excellent strength and corrosion resistance, their thermal shock resistance is still poor. Rapid cooling or heating in the case of rapid temperature changes may cause fine cracks in the material, which further affects the durability and reliability of the refractories. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the embodiments of the present application includes providing a refractory material and a preparation method thereof, and a glass kiln, so as to solve the technical problem of poor thermal shock resistance of refractory materials used in glass kilns in current production.

[0006] In the first aspect, an embodiment of the present application provides a refractory material, comprising, by weight: 40-50 parts of silica sol, 15-20 parts of white corundum, 3-4 parts of aluminum nitride powder, 5-8 parts of silica powder, 3-5 parts of aluminum titanate, 5-8 parts of zirconium oxide, 5-8 parts of barium sulfate, 3-5 parts of borax, 1-2 parts of muscovite powder, 1-2 parts of magnesium oxide and 1-3 parts of butanediol; wherein the mass concentration of silica in each part of silica sol is 40-45%.

[0007] The refractory material provided in this application achieves excellent performance in a high temperature environment through the synergistic effect of multiple raw materials. Among them, the combination of silica sol and silica powder enhances the bonding and density of the material, improves the refractoriness and compressive strength; and the combination of white corundum and aluminum nitride powder provides excellent mechanical strength and thermal conductivity, so that the material has better thermal shock resistance. The combination of zirconium oxide and aluminum titanate further improves the stability and corrosion resistance of the refractory material, which is suitable for applications under extreme conditions. At the same time, the interaction between silica powder and barium sulfate reduces brittleness and enhances refractoriness; the combination of borax and muscovite powder improves the fluidity and thermal insulation of the material and ensures the molding ability. Finally, the combination of magnesium oxide and butanediol optimizes the processing performance and adaptability, so that the entire formula shows a strong comprehensive performance in the preparation and application of refractory materials, making it reliable and durable in high temperature environments. Therefore, through the synergistic effect between the above raw materials, the refractory material has the advantages of high refractoriness, excellent compressive and flexural strength, good thermal shock stability, strong chemical stability and strong adaptability.

[0008] In some embodiments of the present application, the above-mentioned refractory material, calculated by weight, each part of white corundum includes: 28-32 parts of alumina with a particle size of 3-5mm, 37-43 parts of alumina with a particle size of 2-3mm, 18-23 parts of alumina with a particle size of 0.088-2mm, and 8-12 parts of alumina with a particle size less than 0.088mm.

[0009] In this application, through reasonable particle size distribution, the formula of white corundum not only improves the strength, toughness and thermal stability of the refractory material, but also improves fluidity and formability, reduces brittleness and enhances wear resistance. These advantages make the application of the refractory material in high temperature environment more reliable and can meet the high standard requirements of modern industry for refractory materials.

[0010] In some embodiments of the present application, the particle size of aluminum nitride is less than 0.088 mm; the particle size of zirconium oxide is 1-2 mm; the particle size of silicon dioxide is less than 0.088 mm, and the mass proportion of silicon dioxide with a fineness of less than 1 μm is ≥80%.

[0011] By designing the particle sizes of aluminum nitride, zirconium oxide and silicon dioxide within the above range, this refractory material exhibits excellent mechanical properties, high temperature resistance and thermal shock resistance at high temperatures. The use of fine particles increases the density and bonding of the material, while the medium-sized zirconium oxide provides the necessary support, making the overall formula more reliable and durable in high-temperature applications.

[0012] In some embodiments of the present application, the average particle size of silicon dioxide is 0.1-0.3 μm.

[0013] The design of the average particle size of silica to 0.1-0.3μm not only improves the strength and toughness of the refractory material, but also promotes the formation of a dense structure, improves thermal and chemical stability, and enhances fluidity and formability.

[0014] In some embodiments of the present application, the above-mentioned refractory materials, measured in parts by weight, include: 43-46 parts of silica sol, 16-18 parts of white corundum, 3-4 parts of aluminum nitride powder, 6-7 parts of silica powder, 3.5-4.5 parts of aluminum titanate, 6-7 parts of zirconium oxide, 6-7 parts of barium sulfate, 3.5-4 parts of borax, 1-2 parts of muscovite powder, 1-2 parts of magnesium oxide and 1-3 parts of butanediol; wherein the mass concentration of silica in each part of silica sol is 40-45%.

[0015] In a second aspect, an embodiment of the present application provides a method for preparing the above-mentioned refractory material, comprising: stirring and mixing the raw materials according to a ratio, letting them stand to obtain a mixture; heating the mixture under an inert protective atmosphere, cooling and molding the mixture after the heating reaction is completed to obtain a refractory material.

[0016] The refractory material preparation method provided in the present application not only ensures the performance consistency and stability of the material through uniform mixing, standing to promote reaction, inert atmosphere heating, optimized cooling and molding processing, but also improves the high temperature resistance and service life of the refractory material.

[0017] In some embodiments of the present application, the standing time is 3-5 hours.

[0018] By controlling the standing time within the range of 3-5h, the interaction between raw materials can be effectively promoted, the sufficiency of chemical reactions can be improved, bubble generation can be reduced, particle distribution can be optimized, material stability can be maintained, and production efficiency can be improved.

[0019] In some embodiments of the present application, the heating reaction comprises: heating the mixture to 100-120° C. at a heating rate of 5-7° C. / min under an inert protective atmosphere, and keeping the temperature for 2-4 hours.

[0020] By controlling the heating parameters in the heating reaction at 100-120°C, the heating rate at 5-7°C / min, and the insulation time at 2-4h, it is possible to effectively prevent material damage, reduce gas release, promote uniformity of chemical reactions, enhance the formation of refractory structures, reduce internal stress, optimize microstructures, and improve production safety.

[0021] In some embodiments of the present application, the preparation method further comprises: performing annealing after the molding process under an inert protective atmosphere, wherein the cooling rate during the annealing process is 2-4°C / min.

[0022] Controlling the cooling rate within the range of 2-4°C / min during the annealing process can effectively and evenly release internal stress, optimize the microstructure, improve thermal shock resistance, enhance mechanical properties, reduce defect generation, improve production safety, and improve the thermal stability of the material.

[0023] In some embodiments of the present application, the inert protective atmosphere includes nitrogen.

[0024] As an inert protective atmosphere, nitrogen can effectively prevent oxidation, reduce the risk of combustion, maintain component purity, promote uniform heating, reduce costs, have a wide range of applicability, and simplify the production process.

[0025] In a third aspect, an embodiment of the present application provides a glass kiln comprising any of the above-mentioned refractory materials. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0027] A refractory material and a preparation method thereof according to an embodiment of the present application are described in detail below.

[0028] An embodiment of the present application provides a refractory material, which includes, by weight: 40-50 parts of silica sol, 15-20 parts of white corundum, 3-4 parts of aluminum nitride powder, 5-8 parts of silica powder, 3-5 parts of aluminum titanate, 5-8 parts of zirconium oxide, 5-8 parts of barium sulfate, 3-5 parts of borax, 1-2 parts of muscovite powder, 1-2 parts of magnesium oxide, and 1-3 parts of butanediol; wherein the mass concentration of silica in each part of silica sol is 40-45%.

[0029] In the formula of this refractory material, there are multiple synergistic effects between the raw materials, which make the material show excellent performance in high temperature environment. Among them, the silica sol contains 40-45% silica, which can provide good adhesion and enhance the density of the material. Silica powder forms a network structure at high temperature, further enhancing the strength of the refractory material; improving the refractoriness and compressive strength of the material, making it structurally stable at high temperature. White corundum provides excellent mechanical strength and wear resistance, while aluminum nitride powder improves the thermal conductivity and thermal shock resistance of the refractory material. The combination of the two can effectively improve the overall performance of the material; enhance the material's bearing capacity and thermal shock resistance at high temperatures, and reduce the risk of cracking caused by temperature changes. Zirconia has good high temperature resistance and permeability resistance, and aluminum titanate can improve the material's adhesion and wear resistance. The combination of the two enables the refractory material to maintain good stability and strength in high temperature environments; improves the material's corrosion resistance and thermal shock stability, and is suitable for high temperature applications such as glass kilns. Silica powder provides structural support, while barium sulfate can enhance the material's thermal shock resistance and permeability resistance. The combination of the two effectively reduces the brittleness of the material; improves the refractoriness and service life of the material, and reduces the risk of failure at high temperatures. Borax can lower the melting point of the material and improve its fluidity, while muscovite powder increases the heat resistance and thermal insulation of the material. The combination of the two enables the refractory material to exhibit good fluidity and formability at high temperatures; improves the molding ability of the material at high temperatures, enhances its thermal insulation properties, and is suitable for applications that require good thermal insulation effects. Magnesium oxide can enhance the acid resistance and heat resistance of the refractory material, while butanediol, as an additive, can improve the fluidity of the material and reduce the viscosity, which is helpful for mixing and molding; improves the processing performance and adaptability of the material, making it easier to operate during the preparation process and improving the quality of the final product. In summary, through the synergistic effect between the above-mentioned raw materials, the refractory material has at least the following advantages:

[0030] 1. High refractoriness: Silica sol and silicon dioxide enhance the material's ability to withstand high temperatures.

[0031] 2. Excellent compressive and flexural strength: The combination of white corundum and aluminum nitride provides strong structural support.

[0032] 3. Good thermal shock stability: The use of zirconium oxide and aluminum titanate reduces cracking caused by thermal stress.

[0033] 4. Strong chemical stability: Barium sulfate and magnesium oxide improve the corrosion resistance of the material.

[0034] 5. Strong adaptability: By optimizing the formula, the material can be used in a variety of high-temperature application scenarios, such as glass kilns.

[0035] Specifically,

[0036] As a binder, silica sol can significantly improve the slag resistance of refractory materials. This means that refractories using silica sol can better resist erosion when facing high-temperature slag produced during glass melting, thereby maintaining structural stability and extending service life. In addition, silica sol can be used as a binder for pure aluminate cement in amorphous refractory materials, especially in spray coatings, by adding accelerators to adjust the setting time. The use of this binder can shorten the construction time and improve the thermal strength, which is very important for glass kilns in high temperature environments. Compared with organic resins and tar binders, silica sol can greatly reduce environmental pollution. This is particularly important for the glass manufacturing industry today when environmental protection requirements are increasingly stringent. If its content is less than 40wt%, the structural strength of the refractory may be weakened due to the low content, resulting in a decrease in refractoriness; it may also affect the thermal shock resistance of the refractory, making it more likely to break when the temperature changes drastically; at the same time, it may weaken the erosion resistance of the refractory to glass liquid and alkaline flying materials, thereby shortening the service life. If its content is higher than 45wt%, it may cause the internal structure of the refractory material to be too tight, affecting the function of its expansion joints and further affecting the thermal expansion and contraction properties of the refractory material; it may also affect the crystallization transformation of the refractory material during kiln baking and cold repair processes, and appropriate measures are needed to adapt to these changes.

[0037] Aluminum titanate has excellent erosion resistance and can resist the erosion of glass liquid. In glass kilns, refractory materials need to withstand the erosion and corrosion of high-temperature glass liquid for a long time. The addition of aluminum titanate can significantly improve the erosion resistance of refractory materials and extend their service life. The introduction of aluminum titanate can improve the toughness of refractory materials and increase the impact strength. This is crucial for glass kilns, because refractory materials must not only withstand high temperatures, but also withstand the impact of mechanical stress and thermal stress. Aluminum titanate has excellent thermal shock resistance and can remain stable under drastic temperature changes. This is especially important for the start-up and shutdown operations of glass kilns, because frequent temperature changes can cause cracks or even peeling of refractory materials, and the addition of aluminum titanate can significantly improve the thermal shock stability of refractory materials. Aluminum titanate ceramics have the characteristics of low thermal expansion coefficient, which helps to reduce the volume change caused by temperature changes, thereby reducing the thermal stress of refractory materials and further improving their thermal shock resistance. Aluminum titanate ceramics can maintain good performance at high temperatures, which makes it have a wide range of application prospects in high-temperature industrial kilns.

[0038] Barium sulfate has excellent corrosion resistance and can resist the erosion of glass melt. In glass furnaces, refractory materials need to withstand the erosion and corrosion of high-temperature glass melt for a long time. The addition of barium sulfate can significantly improve the corrosion resistance of refractory materials and extend their service life. The introduction of barium sulfate can increase the refractive index and density of glass, and enhance the gloss and chemical stability of the glass surface. The improvement of these physical and chemical properties is of great significance to the quality improvement of glass products. In the glass production process, when BaO is introduced in the form of barium sulfate (BaSO4), the melting rate of the batch can be increased, thereby achieving the purpose of increasing the melting rate. At the same time, sulfur dioxide (SO2) produced by the decomposition of barium sulfate plays an important role in the growth and dissolution of bubbles, which helps to improve the clarification efficiency of glass melt. Barium sulfate can be used as a flux to promote the melting and clarification process of glass by reducing the viscosity and surface tension of glass melt. This helps to reduce bubbles and inclusions in the glass and improve the transparency and quality of the glass. In some cases, barium sulfate can replace other more expensive raw materials, such as barium carbonate or barium hydroxide, thereby reducing production costs. However, it should be noted that substitutions between different raw materials need to take into account their effects on glass composition and properties.

[0039] The introduction of butanediol can improve the physical and chemical properties of refractory materials, making them more stable at high temperatures and thus resistant to erosion by molten glass. This improved erosion resistance helps to extend the service life of refractory materials. The addition of butanediol can improve the toughness and impact strength of refractory materials, which is critical for glass furnaces because refractory materials must not only withstand high temperatures, but also mechanical and thermal stresses. In some cases, butanediol can be used as a binder to help the different components in the refractory materials better combine together, thereby improving the density and overall performance of the refractory materials. As a relatively inexpensive additive, butanediol can improve the performance of refractory materials without significantly increasing costs, which is an important consideration for glass manufacturers.

[0040] Silica has an ultra-microstructure filling effect, which can significantly improve the density and strength of refractory materials. At the same time, it can also improve the fluidity of castable refractory materials, reduce water consumption, make it easier to shape, and thus improve production efficiency. Silica can become a liquid phase at high temperatures, reducing the viscosity of mass transfer between particles, thereby enhancing the mass transfer rate and promoting sintering between particles. This makes the castables added with silica have higher strength and thermal shock resistance at high temperatures. Silica is highly active and is more likely to generate mullite phase in the presence of Al2O3 components. This phase change can improve the high-temperature strength and thermal shock resistance of refractory materials. Extend the service life of refractory materials: Since silica improves the density, high-temperature performance and chemical stability of refractory materials, it can significantly extend the service life of refractory materials, especially in high temperature, high pressure and corrosive environments.

[0041] Aluminum nitride has high hardness and good chemical stability, which enables it to resist the erosion of glass liquid at high temperatures. In glass kilns, refractory materials need to withstand the erosion and corrosion of high-temperature glass liquid for a long time. The addition of aluminum nitride can significantly improve the erosion resistance of refractory materials and extend their service life. The addition of aluminum nitride can also improve the mechanical properties of refractory materials, such as strength and toughness. This is crucial for glass kilns, because refractory materials must not only withstand high temperatures, but also withstand the impact of mechanical and thermal stresses. By using aluminum nitride as an additive or coating material, the dependence on expensive raw materials can be reduced, thereby reducing the production cost of refractory materials. At the same time, since aluminum nitride improves the durability of refractory materials, reduces the frequency of replacement, and further reduces long-term operating costs, the quality of refractory materials directly affects the quality of glass products. The addition of aluminum nitride can improve the purity and uniformity of refractory materials and reduce the impurity content in glass, thereby improving the transparency and quality of glass products.

[0042] Magnesium oxide (MgO) is an important refractory material, which plays a key role in refractory materials for glass kilns. The melting point of magnesium oxide is very high, up to 2800℃, which makes the refractories containing magnesium oxide have extremely high refractoriness, usually above 2000℃. Such refractoriness enables magnesium bricks to maintain stability and durability in high-temperature environments such as glass kilns. Magnesium oxide can significantly improve the slag resistance of refractories, that is, the ability to resist the erosion of high-temperature molten slag. In the glass manufacturing process, refractories need to withstand the erosion of various chemicals, and the addition of magnesium oxide helps to extend the service life of refractories. Magnesium oxide can also improve the thermal shock stability of refractories, that is, the ability to resist cracking caused by sudden temperature changes. Glass kilns experience frequent temperature changes during use. This characteristic of magnesium oxide helps to maintain the structural stability of refractory materials and reduce damage caused by temperature fluctuations. If its content is lower than 1.0wt%, the refractoriness of the refractory may be insufficient due to the low content of magnesium oxide, and it may not be able to withstand the high temperature environment in the glass furnace; it may also affect the structural stability of the refractory at high temperatures, making it easier to melt and deform; and it may shorten its service life. If its content is higher than 2.0wt%, the cost of the refractory may also increase accordingly. Although magnesium oxide can improve the refractoriness and high-temperature structural strength of refractory materials, magnesium oxide with a content higher than 2.0wt% may affect the structural stability of the refractory materials, especially under high temperature and load conditions.

[0043] The role of borax in refractory materials for glass kilns is mainly to improve the performance of refractory materials, especially to enhance their corrosion resistance and improve thermal shock stability. Borax can improve the corrosion resistance of refractory materials, which is crucial for environments such as glass kilns that are exposed to various chemicals at high temperatures. The addition of borax helps to improve the thermal shock stability of refractory materials, enabling them to maintain structural stability under rapid temperature changes and reduce the risk of breakage caused by temperature fluctuations. If its content is less than 3.0wt%, since borax acts as a flux in the glass manufacturing process, too low a content may cause insufficient melting of the glass, thereby affecting the quality and uniformity of the glass. Borax can reduce the melting temperature of glass. If the content is insufficient, a higher temperature may be required to achieve the same melting effect, thereby increasing energy consumption; if its content is higher than 5.0wt%, since borax is corrosive, too high a content may aggravate the chemical erosion of refractory materials, resulting in a decrease in the performance of refractory materials; excessive borax may affect the structural stability of refractory materials, especially under the dual effects of high temperature and chemical reaction.

[0044] Muscovite can maintain stable physical and chemical properties under high temperature environment, and its melting point is as high as over 1000 degrees Celsius, which enables it to maintain its structure and performance under high temperature conditions of glass furnace. Because muscovite has a low thermal expansion coefficient and thermal conductivity, it can effectively resist the influence of thermal shock and thermal stress, which is especially important for glass furnaces that are often affected by temperature changes. Muscovite has good corrosion resistance and can resist the erosion of corrosive media such as acids and alkalis, which helps to extend the service life of refractory materials and reduce maintenance costs. If its content is less than 1.0wt%, it may cause the refractoriness of refractory materials to be insufficient and unable to withstand the high temperature environment in the glass furnace; it may also affect the thermal shock resistance of refractory materials, making them more likely to break when the temperature changes suddenly; at the same time, it may shorten the service life; if its content is higher than 2.0wt%, it may unnecessarily increase the cost of refractory materials; and excessive muscovite may affect the structural stability of refractory materials, especially under high temperature and load conditions.

[0045] Zirconia plays a major role in enhancing the performance and corrosion resistance of refractory materials for glass kilns. Adding zirconium oxide can improve the thermal shock resistance of refractory materials, which is particularly important for glass kilns that are often affected by high temperature changes. Zirconia can improve the mechanical strength of refractory materials, which means that refractory materials can withstand greater physical pressure and reduce the possibility of wear and damage. By adding zirconium oxide, the thermal expansion coefficient of refractory materials can be effectively reduced, which helps to maintain the stability of the structure when the temperature changes. Zirconia has good corrosion resistance, protects refractory materials from being easily corroded by acids, alkalis and other oxides, and maintains durability in high temperature environments. If its content is less than 5.5wt%, it may reduce the refractoriness of the refractory material, making it unable to withstand the high temperature environment in the glass kiln; it may also affect the thermal shock resistance of the refractory material, making it more likely to break when the temperature changes drastically. Zirconia is one of the oxides with the strongest resistance to glass corrosion, and too low a content may also cause the refractory material to have a reduced resistance to chemical corrosion. Although adding 5.0wt% to 8.0wt% of zirconium oxide can make mullite crystals smaller and the material structure dense, if it is higher than 8.0wt%, the content is too high and may affect the structural stability of the refractory material, especially under high temperature and load conditions; and the cost of the refractory material may also increase accordingly.

[0046] In the present application, each portion of white corundum includes, by weight: 28-32 portions of alumina with a particle size of 3-5 mm, 37-43 portions of alumina with a particle size of 2-3 mm, 18-23 portions of alumina with a particle size of 0.088-2 mm, and 8-12 portions of alumina with a particle size of less than 0.088 mm.

[0047] The present application forms a good particle size gradation by combining alumina of different particle sizes (3-5mm, 2-3mm, 0.088-2mm and <0.088mm). Among them, larger particles (such as 3-5mm and 2-3mm) provide good skeleton support and compressive strength, while smaller particles (such as 0.088-2mm and <0.088mm) can fill the gaps between larger particles, enhancing the density and overall strength of the material. This multi-level particle size ratio makes the material have higher compressive strength and better crack resistance. Because large particles provide higher bearing capacity, small particles improve the toughness of the material by increasing the contact area and changing the stress transfer path, making it less likely to break under external impact or thermal stress. Therefore, this formula can effectively improve the strength and toughness of refractory materials and reduce the risk of cracking under high temperature or load conditions.

[0048] In addition, larger particles are less likely to melt at high temperatures, while smaller particles help form a dense microstructure and reduce thermal stress concentration. This allows the material to maintain good structural integrity in a high-temperature environment, thereby increasing its service life. Therefore, the particle size design of the above-mentioned white corundum helps to improve the stability and fire resistance of the material at high temperatures. At the same time, smaller particles are able to fill the gaps between larger particles, reduce the viscosity of the material, and improve its fluidity. This allows the material to flow and fill the mold better during pouring or press molding, ensuring molding quality. The diversity of particle sizes improves the fluidity of the material and facilitates uniform distribution during the molding process.

[0049] In addition, the presence of small particles can reduce brittle failure caused by stress concentration by increasing the toughness and ductility of the material. This is particularly important for the performance of refractory materials under high temperatures and rapid temperature changes. Therefore, through the above reasonable particle size combination, the brittleness of the material can be effectively reduced. Large particles provide higher wear resistance, while small particles increase the density of the material, making the overall structure stronger and better able to resist wear and corrosion. Therefore, the multi-particle size structure of the above white corundum helps to improve the wear resistance of refractory materials.

[0050] In the present application, the particle size of aluminum nitride is less than 0.088 mm; the particle size of zirconium oxide is 1-2 mm; the particle size of silicon dioxide is less than 0.088 mm, and the mass proportion of silicon dioxide with a fineness of less than 1 μm is ≥80%.

[0051] The particle size of aluminum nitride is controlled to less than 0.088mm. The fine aluminum nitride particles have a large specific surface area and can better contact with other components to form a good interface. This enhanced interface bonding force allows the material to maintain good mechanical properties at high temperatures and reduce the risk of cracking. In addition, fine particles can fill the gaps between large particles and improve the density of the material. Therefore, fine-grained aluminum nitride can improve the overall strength and toughness of the material.

[0052] The particle size of zirconium oxide is controlled to 1-2mm (medium particle size). The larger zirconium oxide particles show excellent thermal stability and resistance to melting at high temperatures, and can effectively resist cracking caused by thermal stress. The larger particle size also makes the structure of the material more supportive and rigid, which helps to improve the compressive strength of the overall refractory material. Therefore, medium-sized zirconium oxide can provide superior high temperature resistance and thermal shock resistance.

[0053] The particle size of silica is controlled to be less than 0.088mm, of which the proportion of fineness less than 1μm is ≥80%. The fine silica particles can form a dense network structure at high temperature, helping to enhance the overall strength of the material and reduce the porosity. Silica of this fineness can effectively fill the gaps between other particles in the mixture, improving the density and impermeability of the material. In addition, fine-particle silica can provide better melting behavior at high temperatures, which helps to form a uniform refractory structure. Therefore, silica with high fineness enhances the adhesion and refractory properties of the material.

[0054] In summary, the fine aluminum nitride and silicon dioxide particles can fill the gaps of large particles of zirconium oxide to form a dense composite material structure, reducing the brittleness of the material and improving its toughness. The larger particles of zirconium oxide provide structural support, while the fine particles enhance the material's crack resistance and wear resistance. The particle size design of the three materials in this application complements each other and improves the comprehensive performance of the refractory material.

[0055] In the present application, the average particle size of silicon dioxide is 0.1-0.3 μm. The silicon dioxide particles obtained within this particle size range help to enhance the overall strength of the refractory material, can fill the gaps between other larger particles, and form a denser microstructure. At the same time, at high temperatures, fine-grained silicon dioxide can form a uniform molten phase, help the material maintain good structural integrity, reduce thermal stress concentration, and avoid cracking and deformation of the material. Moreover, silicon dioxide with high fineness has excellent chemical stability and can resist erosion by a variety of chemical substances. Smaller particle sizes reduce the viscosity of the material and enhance fluidity, so that the material can better fill the mold during casting or compression molding to ensure molding quality. At high temperatures, fine particles can more easily form a molten state, promote uniform melting of the material, prevent local overheating, and help enhance the thermal shock resistance of the material.

[0056] The preparation method of the above refractory material is further described below.

[0057] The present invention provides a method for preparing a refractory material, comprising the following steps:

[0058] Step (1): Raw material preparation

[0059] Prepare various raw materials according to the formula ratio, including silica sol, white corundum, aluminum nitride powder, silicon micropowder, aluminum titanate, zirconium oxide, barium sulfate, borax, muscovite powder and magnesium oxide.

[0060] Step (2): Mixing and stirring

[0061] Particle classification: First, the raw materials with a particle size of >1mm (such as white corundum and zirconium oxide, etc.) are preliminarily screened to make the particle size distribution uniform. Preliminary screening of raw materials with a particle size of >1mm to make the particle size distribution uniform helps to improve the density and strength of the material.

[0062] Preliminary mixing: Place the raw materials >1mm into the mixing equipment and mix thoroughly to make the ingredients evenly distributed.

[0063] Add silica sol: slowly add silica sol into the mixture, stir evenly, and make it fully penetrate into the surface of particles. The addition of silica sol strengthens the bonding force between particles and improves the overall strength of the material.

[0064] Add fine powder: After the silica sol is evenly mixed, gradually add fine powder (such as aluminum nitride powder, silicon powder, etc.), and continue stirring to fully mix all the ingredients. The addition of fine powder can increase the reactivity of the material, promote the uniform reaction of the ingredients, and improve the physical properties of the final product.

[0065] Standing: After mixing, the mixture is allowed to stand for 3-5 hours to promote interaction and chemical reaction between the raw materials and prepare for the subsequent steps. The standing time enhances the interaction between the raw materials, helps to form a more stable bond, and improves the efficiency and effect of the subsequent heating reaction.

[0066] Step (3): Heat treatment

[0067] Electric furnace preparation: Before heating, clean the inside of the electric furnace to avoid contamination.

[0068] Temperature control: In an inert protective atmosphere (such as nitrogen), the mixed material is heated from room temperature to 100-120°C, and the heating rate is controlled at 5-7°C / min to prevent damage to the raw materials or gas release caused by rapid heating. Controlling the heating rate within the above range can reduce or avoid damage to the material or gas release caused by rapid heating, and make the raw materials have a certain stability during the heating process.

[0069] Insulation treatment: After reaching the specified temperature, keep it at this temperature for 2-4 hours to allow the components in the mixture to fully react and form a preliminary refractory structure. Insulation at the specified temperature helps the material components to fully react, form a preliminary refractory structure, and improve the strength and fire resistance of the material.

[0070] Cooling process: After the insulation is completed, the mixture is gradually cooled to 70°C to reduce the impact of temperature changes on the mixture structure and prevent the material from cracking or deformation. Gradual cooling can reduce the impact of temperature changes on the material structure and reduce the risk of cracking or deformation caused by thermal stress.

[0071] Step (4): Cooling and annealing

[0072] Mould preparation: Before pouring, the prefabricated mould should be dried and cleaned to ensure the molding quality of the refractory material. A dry and clean mould can ensure that the refractory material forms a good shape and structure during the pouring process and improve the yield.

[0073] Pouring: Carefully pour the mixture cooled to 70°C into the prefabricated mold, making sure that the pouring is even and without bubbles. Careful pouring ensures that the material fills the mold evenly, reduces bubbles, and improves the density and strength of the finished product.

[0074] Cooling and annealing: In an inert protective atmosphere, the mixture in the mold is cooled and annealed, and the cooling rate is controlled at 3°C / min to ensure that the internal stress of the material is evenly released and a more stable refractory material structure is obtained. Controlling the cooling rate within the above range can evenly release the internal stress of the material and improve the stability and thermal shock resistance of the material.

[0075] Inspection of finished products: After annealing, the appearance and performance of the refractory materials are inspected to ensure that they meet the requirements of the glass furnace. Through appearance and performance inspection, the finished products can meet the design requirements, meet the use standards of the glass furnace, and improve the reliability of the products.

[0076] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0077] Example 1

[0078] This embodiment provides a refractory material, and the preparation method thereof is as follows:

[0079] (1) Prepare the following raw materials:

[0080] 500kg of silica sol (mass concentration of silicon dioxide is 42%), 180kg of white corundum, 30kg of aluminum nitride powder (particle size <0.088mm), 60kg of silicon dioxide powder (particle size <0.088mm), 30kg of aluminum titanate, 60kg of zirconium oxide (particle size 1-2mm), 60kg of barium sulfate, 30kg of borax, 20kg of muscovite powder, 20kg of magnesium oxide, and 10kg of butanediol; wherein, each 1kg of white corundum particles comprises: 30% of aluminum oxide with a particle size of 5-3mm, 40% of aluminum oxide with a particle size of 3-2mm, 20% of aluminum oxide with a particle size of 2-0.088mm, and 10% of aluminum oxide with a particle size <0.088mm.

[0081] (2) First, mix and stir the material with a particle size greater than 1 mm, then add the silica sol and stir evenly, and finally add the fine powder and mix evenly, and then let the material stand for 3.5 hours to obtain a mixed material;

[0082] (3) The mixture is placed in an electric heating furnace. Under nitrogen protection, the mixture is heated from room temperature to 110°C at a rate of 5°C / min. The mixture is kept at 110°C for 3 hours. After the heat preservation is completed, the mixture is gradually cooled to 70°C and poured into a prefabricated mold.

[0083] (4) Under nitrogen protection, the mixture in the mold is cooled and annealed, and the cooling rate during the annealing process is 3°C / min, thereby obtaining a refractory material suitable for use in a glass kiln.

[0084] Example 2

[0085] This embodiment provides a refractory material, and the preparation method thereof is as follows:

[0086] (1) Prepare the following raw materials:

[0087] 470kg of silica sol (mass concentration of silicon dioxide is 42%), 170kg of white corundum, 30kg of aluminum nitride powder (particle size <0.088mm), 70kg of silicon dioxide powder (particle size <0.088mm), 40kg of aluminum titanate, 80kg of zirconium oxide (particle size 1-2mm), 60kg of barium sulfate, 30kg of borax, 20kg of muscovite powder, 20kg of magnesium oxide, and 10kg of butanediol; wherein, each 1kg of white corundum particles comprises: 30% of aluminum oxide with a particle size of 5-3mm, 40% of aluminum oxide with a particle size of 3-2mm, 20% of aluminum oxide with a particle size of 2-0.088mm, and 10% of aluminum oxide with a particle size <0.088mm.

[0088] (2) First, mix and stir the material with a particle size greater than 1 mm, then add the silica sol and stir evenly, and finally add the fine powder and mix evenly, and then let the material stand for 3.5 hours to obtain a mixed material;

[0089] (3) The mixture is placed in an electric heating furnace. Under nitrogen protection, the mixture is heated from room temperature to 110°C at a rate of 5°C / min. The mixture is kept at 110°C for 3 hours. After the heat preservation is completed, the mixture is gradually cooled to 70°C and poured into a prefabricated mold.

[0090] (4) Under nitrogen protection, the mixture in the mold is cooled and annealed, and the cooling rate during the annealing process is 3°C / min, thereby obtaining a refractory material suitable for use in a glass kiln.

[0091] Example 3

[0092] This embodiment provides a refractory material, and the preparation method thereof is as follows:

[0093] (1) Prepare the following raw materials:

[0094] 450kg of silica sol (mass concentration of silicon dioxide is 42%), 180kg of white corundum, 35kg of aluminum nitride powder (particle size <0.088mm), 65kg of silicon dioxide powder (particle size <0.088mm), 40kg of aluminum titanate, 65kg of zirconium oxide (particle size 1-2mm), 65kg of barium sulfate, 40kg of borax, 20kg of muscovite powder, 20kg of magnesium oxide, and 20kg of butanediol; wherein, each 1kg of white corundum particles comprises: 30% of aluminum oxide with a particle size of 5-3mm, 40% of aluminum oxide with a particle size of 3-2mm, 20% of aluminum oxide with a particle size of 2-0.088mm, and 10% of aluminum oxide with a particle size <0.088mm.

[0095] (2) First, mix and stir the material with a particle size greater than 1 mm, then add the silica sol and stir evenly, and finally add the fine powder and mix evenly, and then let the material stand for 3.5 hours to obtain a mixed material;

[0096] (3) The mixture is placed in an electric heating furnace. Under nitrogen protection, the mixture is heated from room temperature to 110°C at a rate of 5°C / min. The mixture is kept at 110°C for 3 hours. After the heat preservation is completed, the mixture is gradually cooled to 70°C and poured into a prefabricated mold.

[0097] (4) Under nitrogen protection, the mixture in the mold is cooled and annealed, and the cooling rate during the annealing process is 3°C / min, thereby obtaining a refractory material suitable for use in a glass kiln.

[0098] Please see Table 1 for other embodiments and comparative examples.

[0099] Table 1

[0100]

[0101]

[0102] Among them, Example 7 is basically the same as Example 1, except that the composition of the white corundum particles is different. Each 1kg of white corundum particles includes: 40% alumina with a particle size of 5-3mm, 25% alumina with a particle size of 3-2mm, 30% alumina with a particle size of 2-0.088mm, and 5% alumina with a particle size of less than 0.088mm.

[0103] Example 8 is basically the same as Example 3, except that the composition of the white corundum particles is different. Each 1kg of white corundum particles includes: 30% alumina with a particle size of 5-3mm, 38% alumina with a particle size of 3-2mm, 12% alumina with a particle size of 2-0.088mm, and 20% alumina with a particle size of less than 0.088mm.

[0104] Test example

[0105] This test example conducts performance tests on the refractory materials prepared in the above-mentioned Examples 1-8 and Comparative Examples 1-6, including load softening temperature, room temperature compressive strength, abrasion, and thermal shock resistance.

[0106] The load softening temperature is tested by a load softening instrument; the room temperature compressive strength...; and the wear is tested by a Taber wear tester. The test of thermal shock resistance adopts the following method: the refractory material is treated at 1450℃ for 3h to measure its high temperature flexural strength, then kept at 1100℃ for 20min and then quenched in 20℃ cold water, repeated 30 times, and its low temperature flexural strength is measured.

[0107] Please see Table 2 for the above performance test results.

[0108] Table 2

[0109]

[0110] As can be seen from Table 2, by comparing Example 7 and Example 8, it can be seen that the ratio of the white corundum component provided in the present application is more conducive to improving; by comparing Comparative Example 1 and Comparative Example 2, it can be seen that the ratio of white corundum and aluminum nitride powder provided in the present application is more conducive to improving the corrosion resistance of refractory materials, extending their service life, and improving the mechanical properties of refractory materials; by comparing Comparative Example 3 and Comparative Example 4, it can be seen that the ratio of zirconium oxide and aluminum titanate provided in the present application is more conducive to improving the corrosion resistance and thermal shock resistance of refractory materials; by comparing Comparative Example 5 and Comparative Example 6, it can be seen that the ratio of muscovite powder and borax provided in the present application is more conducive to improving the corrosion resistance and thermal shock resistance of refractory materials.

[0111] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. A refractory material, characterized in that: In parts by weight, it includes: 40-50 parts of silica sol, 15-20 parts of white corundum, 3-4 parts of aluminum nitride powder, 5-8 parts of silicon dioxide powder, 3-5 parts of aluminum titanate, 5-8 parts of zirconium oxide, 5-8 parts of barium sulfate, 3-5 parts of borax, 1-2 parts of muscovite powder, 1-2 parts of magnesium oxide and 1-3 parts of butanediol; Wherein, the mass concentration of silicon dioxide in each portion of the silica sol is 40-45%.

2. The refractory material according to claim 1, characterized in that In terms of weight, each portion of the white corundum comprises: 28-32 portions of aluminum oxide with a particle size of 3-5 mm, 37-43 portions of aluminum oxide with a particle size of 2-3 mm, 18-23 portions of aluminum oxide with a particle size of 0.088-2 mm, and 8-12 portions of aluminum oxide with a particle size of less than 0.088 mm.

3. The refractory material according to claim 1, characterized in that: The particle size of the aluminum nitride is less than 0.088 mm; the particle size of the zirconium oxide is 1-2 mm; the particle size of the silicon dioxide is less than 0.088 mm, and the mass proportion of the silicon dioxide with a fineness of less than 1 μm is ≥ 80%; Optionally, the average particle size of the silicon dioxide is 0.1-0.3 μm.

4. The refractory material according to any one of claims 1 to 3, characterized in that: In parts by weight, it includes: 43-46 parts of silica sol, 16-18 parts of white corundum, 3-4 parts of aluminum nitride powder, 6-7 parts of silicon dioxide powder, 3.5-4.5 parts of aluminum titanate, 6-7 parts of zirconium oxide, 6-7 parts of barium sulfate, 3.5-4 parts of borax, 1-2 parts of muscovite powder, 1-2 parts of magnesium oxide and 1-3 parts of butanediol; The mass concentration of silicon dioxide in each portion of the silica sol is 40-45%.

5. A method for preparing a refractory material according to any one of claims 1 to 4, characterized in that: include: The raw materials are stirred and mixed according to the proportions, and allowed to stand to obtain a mixture; The mixed material is subjected to a heating reaction under an inert protective atmosphere, and after the heating reaction is completed, the mixed material is cooled and molded to obtain the refractory material.

6. The preparation method according to claim 5, characterized in that: The standing time is 3-5h.

7. The preparation method according to claim 5, characterized in that: The heating reaction comprises: Under an inert protective atmosphere, the mixture is heated to 100-120° C. at a heating rate of 5-7° C. / min and kept warm for 2-4 hours.

8. The preparation method according to any one of claims 5 to 7, characterized in that: Also includes: In an inert protective atmosphere, the molding process is followed by an annealing process, wherein the cooling rate during the annealing process is 2-4°C / min.

9. The preparation method according to claim 8, characterized in that: The inert protective atmosphere includes nitrogen.

10. A glass furnace, characterized in that: The refractory material comprises the refractory material according to any one of claims 1 to 4.